Omprog as Inspiration for Evening Wear Gala Creation - Maylani, Rima; Arifiana, Deny; Marniati, Marniati; Mayasari, Peppy (PT. Riset Press International, 2025)
Omprog, or the crown of the seblang dancer in the Seblang ritual ceremony in Olehsari, Banyuwangi, became the main inspiration for the creation of gala evening wear. The purpose of this creation is one of the creative ways in fashion design that can enrich the wardrobe by blending culture with modern style. The method used to achieve this goal involves four stages: exploration, design, realization, and presentation, by applying the exploration results of techniques and materials to produce appropriate details. This creation is inspired by the artist's belief that Omprog possesses a beautiful, unique, and mystical visual form and has yet to be conceptualized by previous designers. The type of practice-led research approach that underpins the creation of this work was conducted through a study of fashion design studio practices focusing on